(untitled) (International Journal of Engineering and Computer Science, 2017)
Embedded zero tree wavelet(EZW) coding is a very effective and computationally simple technique for image compression. Here we present a new and different implementation based on set partitioning in hierarchical trees(SPIHT).It is based on the principles of partial ordering by magnitude with a set partitioning sorting algorithm, ordered bit plane transmission and exploitation of self similarity across different scales of an image wavelet transform. The image coding results calculated from actual file sizes and images reconstructed by the decoding algorithm are either comparable to or surpass previous results obtained through much more sophisticated and computationally complex methods. In addition, the new coding and decoding procedures are extremely fast, and they can be made even faster, with only small loss in performance, by omitting entropy coding of the bit stream by arithmetic coding. It can be used for future still and moving image coding systems. Additional features required for this include fidelity and resolution scalability, region of interest enhancement, random access decoding, resilience to errors due to channel noise or packet loss, fast encoding and/or decoding speed and low computational and hardware complexity.